Partisan Alignment Effects on Total Factor Productivity. Issue 1 (2nd January 2016) - Aray, Henry
Abstract : Aray H. Partisan alignment effects on total factor productivity, Regional Studies . Unlike the literature on political effects on real economy that suggests that partisan effects accrue through aggregate demand, it is hypothesized that such effects could also accrue through aggregate supply. Using panel data for the Spanish regions over the 1986–2010 period, the main results are: (1) partisan alignment effects only arise when central government enjoys a majority; (2) there exist a positive contemporaneous effect and negative lagged effects; and (3) in absolute value, such effects vanish over time. Results are robust to different specifications and measures of total factor productivity (TFP) and methods of estimation.